429 National Evaluation of Confidence and Preparedness for Surgical Rotations in Medical Students and Foundation Year Doctors. (4th May 2021) - Tan, L; Mullins, W; Gargan, A; Townsend, J; Gargan, K; Brice, J; Shea, J; Jang, C; Shukla, S; Asif, A; Fricker, M; Mohan, M; et al.
Abstract: Introduction: Limited published and anecdotal evidence suggests foundation year (FY) doctors start their surgical rotations with lower confidence than medical rotations. This may be due to insufficient undergraduate practical teaching related to common surgical rotations. This study aimed to evaluate the confidence and preparedness for surgical rotations of medical students and FY doctors. Method: An expert-validated questionnaire was distributed nationally to UK medical students and FY doctors. The primary outcome was confidence in completing common tasks during surgical rotations. Results: 491 participants (84% medical students, 16% FYs) were recruited from 36 UK medical schools. 80% were likely to pursue a career in surgery however only 7% felt confident about starting a surgical FY job. 66% felt neutral or unsatisfied about the quality of medical school surgical teaching, and 80% indicated that placements did not prepare them well to manage common FY surgical tasks. The internal reliability of the questionnaire was high (=0.939). Conclusions: Medical students and FY doctors lack confidence and preparation for surgical jobs. High-quality, practically grounded educational courses such as the National Surgical Teaching Society (NSTS) webinar curriculum could improve confidence and preparedness for surgical rotations. Further research evaluating the benefits of such courses is warranted.